2018
DOI: 10.1002/sim.7958
|View full text |Cite
|
Sign up to set email alerts
|

Interim monitoring using the adaptively weighted log‐rank test in clinical trials for survival outcomes

Abstract: For testing treatment effect with survival data, the log-rank test has been the method of choice and enjoys an optimality property under proportional hazards alternatives. However, there can be significant loss of power in a variety of nonproportional situations. Yang and Prentice proposed an adaptively weighted log-rank test that improves the power of the log-rank test over a wide range of hazard ratio scenarios. In clinical trials, the data and safety monitoring board typically monitors the trial results per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Often, its empirical size is greater than the nominal level, especially under small sample size (see the Supplementary Material). In a recent work of Yang, 17 which deals with interim monitoring using adaptive weighted log-rank test, the author suggests using the re-sampling method of Lin et al. 18 instead of the original asymptotic approach, 18 for improving the type I error rate.…”
Section: Simulation Studymentioning
confidence: 99%
“…Often, its empirical size is greater than the nominal level, especially under small sample size (see the Supplementary Material). In a recent work of Yang, 17 which deals with interim monitoring using adaptive weighted log-rank test, the author suggests using the re-sampling method of Lin et al. 18 instead of the original asymptotic approach, 18 for improving the type I error rate.…”
Section: Simulation Studymentioning
confidence: 99%
“…Let us look at the interim data from SPRINT at the last 3 looks, collected at roughly the information time of 0.30, 0.41, and 0.54. If we use a spending function that takes the values .00024, .00139, and .00535 at those 3 looks, the values used in the trial, then it was shown that the adaptively weighted log‐rank test would cross the boundary at the last 2 looks, agreeing with the log‐rank test and the test used in the trial …”
Section: Examplesmentioning
confidence: 74%
“…It was noted in the literature that, for some cases with moderate sample size, the approach of interpolation with tabular values for the adaptively weighted log‐rank test may result in somewhat inflated size. In Yang a resampling method was used to calculate the critical value, which results in better control of the type 1 error rate while still maintaining overall improvement of the log‐rank test. Interim testing procedures were also developed for group sequential monitoring of clinical trials using the adaptively weighted log‐rank test.…”
Section: Testing the Treatment Effectmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 The Kaplan–Meier method was adopted for survival analysis, and the Log rank test was used to test the significance of differences between groups. 22 , 23 The factors affecting the prognosis of RC were measured by univariate and multivariate Cox regression models. 24 Multivariate analysis was conducted with all factors of P < 0.05 in the univariate.…”
Section: Methodsmentioning
confidence: 99%